Efficient administrative management strategy for activities in international higher education institutions: Lessons for Vietnam - Thang, Pham Dinh; Tuyen, Tran Quang (International research journal of management, IT and social sciences, 2023)
This research article examines the significance of efficient administrative management in international higher education institutions and addresses the specific challenges faced in managing activities effectively. The objective of this study is to propose an administrative management strategy tailored to the context of Vietnam’s international higher education institutions. Drawing upon existing literature, theoretical frameworks related to organizational management, leadership, governance, and strategic planning are explored to inform the development of the strategy. The unique characteristics and challenges of the Vietnamese higher education system, particularly in relation to internationalization efforts, are described, highlighting the importance of aligning administrative management strategies with local context while incorporating international best practices. Essential components of an efficient administrative management strategy, including organizational structure, decision-making processes, resource allocation, staff development and training, technology integration, and quality assurance, are identified and discussed in detail. Successful case studies and best practices from international higher education institutions are analyzed, providing valuable lessons and insights that are relevant and applicable to the Vietnamese context. Specific recommendations and guidelines are provided for Vietnamese higher education institutions seeking to enhance their administrative management practices, considering cultural, institutional, and regulatory factors.